Fatal Encounters - Deanna Jacobsen Koepke; David Thomas; Alexis Manning (Research in Social Sciences and Technology- OpenED Network, 2019)
Research has been conducted for several decades on the framing of stories in the media. This article looks at the way newspaper articles report on and frame the deaths of unarmed people of color at the hands of law enforcement and security personnel from 1999-2017 to determine if local and national print media frame these stories using similar terminology and concepts. Tabular, graphical, and statistical analysis all demonstrate that local and national newspapers do not use similar terminology and concepts.